Antiobesity, Antihyperglycemic, and Antidepressive Potentiality of Rice Fermented Food Through Modulation of Intestinal Microbiota - Hor, Papan Kumar; Pal, Shilpee; Mondal, Joy; Halder, Suman Kumar; Ghosh, Kuntal; Santra, Sourav; Ray, Mousumi; Goswami, Debabrata; Chakrabarti, Sudipta; Singh, Somnath; Dwivedi, Sanjai K.; Takó, Miklós; et al. (Frontiers in Microbiology, 2022)
This study aimed to evaluate the antiobesity, antihyperglycemic, and anti-depressive potentiality of Asparagus racemosus starter-based rice fermented foods. The fermented rice was enriched with multi-strains food graded bacteria like Lactobacillus (29.44%), unclassified (22.89%), Brevundimonas (16.21%), Stenotrophomonas (6.18%), Pseudomonas (3.11%), Bacillus (2.88%), and others minor groups (<2%) analyzed through high-throughput NGS methodology. Eight-week administration of rice fermented food improved food intake, whole-body weights, organs, and different fat masses, serum lipid profiles, and histology of liver and adipose tissue in HFD-induced obese mice. In addition, upregulation of fatty acid oxidation in contrary down-regulation of adipocytogenesis and lypogenesis related genes along with the expression of their regulatory nuclear factors like PPARα, γ, δ and SREBP-1c were also noted. Fermented food also decreased fasting blood glucose, improved glucose and insulin tolerance, and expression of GLUT 4 receptor. The antiobesity and antihyperglycemic effects are also supported by the changes in insulin, leptin, and adiponectin hormones levels. The RT-PCR and DGGE analysis clearly demonstrated that the fermented food facilitated intense colonization of Bacteroids, Lactobacillus, and Bifidobacterium and suppressed the growth of Proteobacteria and Firmicutes in the gut. These latter groups of microorganisms likely modulate the levels of short-chain fatty acids (SCFAs) in intestine like levels of acetate, butyrate, and propionate more than 2 folds. The impairment of memory-learning and anxiety-like obesity-associated cognitive phenotypes were significantly (p< 0.01) mitigated by the action of fermented food. Thus the formulated fermented food can be used as a natural therapeutics to alleviate obesity and its associated psychological and pathophysiological ailments.